Pengaruh Kedisiplinan Belajar dan Lingkungan Teman Sebaya Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII Di SMP Negeri 2 Kauman Tulungagung - Nerlis Cholifah; Yudi Krisno Wicaksono (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to determine the influence of learning discipline and peer environment on student learning outcomes in grade VIII social studies subjects at SMP Negeri 2 Kauman Tulungagung both partially and simultaneously. This research uses a quantitative approach with Ex-post Facto research type. The population in this research was grade VIII students at SMP Negeri 2 Kauman Tulungagung and 89 students were billed as a sample with proportional random sampling technique. Data collection techniques use questionnaires and documentation, while the data analysis used is multiple linear regression. The results showed that: 1) Learning discipline has a positive and significant effect on learning outcomes. 2) The peer environment positively and significantly affects learning outcomes. 3) Learning discipline and peer environment simultaneously have a positive and significant effect on learning outcomes. The Coefficient of Determination (R2) of the two independent variables is 0.625 or 62.5% of student learning outcomes in class VIII social studies subjects at SMP Negeri 2 Kauman Tulungagung. Keywords: Learning Discipline, Peer Environment, and Learning Outcomes